Efektivitas Pemupukan Nitrogen Terhadap Pertumbuhan dan Kandungan Klorofil Kopi Gold Robusta - Oria Alit Farisi; Distiana Wulanjari; Muhammad Ghufron Rosyady; Muhammad Burhanuddin Irsyadi; Moh Alaika Nurul Hak (Vegetalika, 2025)
Coffee is one of the important plantation commodities that plays a significant role in the Indonesian economy. Gold Robusta coffee is a potential genotype currently being developed in Jember, particularly by the University of Jember, as an alternative to the common practice of using seedling cuttings with unidentified genetic origins. This study aimed to determine the optimal nitrogen (urea) dosage containing 46% N and its growth response on immature (TBM) Gold Robusta coffee plants. The research was conducted at the Experimental Field in Darsono Village, Arjasa District, Jember Regency, from May to December 2024. The experimental design used a Completely Randomized Design (CRD) with a single factor, consisting of three levels of urea fertilizer doses, namely 15 g, 30 g, and 45 g/plant, each replicated nine times. Observed variables included plant height, number of leaves, stem diameter, number and length of productive branches, leaf area, and chlorophyll content. Data were analyzed using ANOVA, and significant differences were further tested with Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that urea application significantly affected the growth of immature Gold Robusta coffee. A dose of 45 g/plant produced the best growth performance with an average plant height of 112.78 cm, 21.44 leaves, leaf area of 163.56 cm², and productive branch length of 47 cm. Therefore, urea application at 45 g/plant can be recommended as a fertilizer guideline during the immature phase of Gold Robusta coffee.